(untitled) (Medical Forum Monthly, 2024)
Objective: To study the role of vitamin ‘C’ on X-irradiated epidermis of Guinea pigs under light microscope. Study Design: A prospective experimental study. Place and Duration of Study: This study was conducted at the Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre Karachi 2008 to 2009. Materials and Methods: Twenty seven animals were taken and were divided in to three groups. Each group was further subdivided into three subgroups containing three animals each according to the time of sacrifice i.e. 48 hours, 15th day and 45th day respectively. A single whole body x–irradiation in a dose of 5 Gy was given. Group C animals were also given injection of vitamin-C intraperitoneally in the dose of 1 mg/G/day. Animals were sacrificed under ether anaesthesia after completion of their respective periods. Tissues were processed and 4-5 micron thick paraffin embedded sections were cut and stained with Hematoxylin and eosin Results: Decrease in epidermal thickness was observed in Group B1 animals. Which is highly significant (P < 0.001) when compared to control. Results of animals of Group B2, and B3 were non significant (P > 0.05) when compared to control. Non significant results were obtained when Group C was compared to control group. Conclusion: X-irradiation damages the epidermis and vitamin ‘C’ minimizes the damaging effects.